Dr. ENHANCING WEED CONTROL EFFICACY OF TWO PREEMERGENCE HERBICIDES IN MAIZE/ JACKBEANS AND MAIZE/GROUNDNUT INTERCROP IN DERIVED SAVANNA AGRO-ECOLOGY: WEED CONTROL EFFICACY OF TWO PREEMERGENCE HERBICIDES IN MAIZE/ JACKBEANS AND MAIZE/GROUNDNUT INTERCROP IN DERIVED SAVANNA AGRO-ECOLOGY - Adeyemi, Olusegun Raphael; Eni, Enor; Lagoke, Toyosi Olayiwola; Ebenezer, Osebekwin (Journal of Agricultural Sciences (Belgrade), 2021)
The inability of pre-emergence herbicides alone to give season-long weed control in maize production justifies the need for supplementary weed control. Field trials were conducted to evaluate intercropped groundnut and jackbean for enhanced weed control efficacy of two pre-emergence herbicides in maize production, in 2013/2014 and 2015 cropping seasons at Federal University of Agriculture, Abeokuta, Nigeria. The experiment was arranged in split-plot fitted in a Randomized Complete Block Design with three replications. Main plots consisted of eight weed control treatments of commercially formulated mixture of Prometryne (20%) + Metolachlor (20%);   Prometryne (13%) + Acetochlor  (38%) each at 2.4 kg a.i/ha, 1.6 kg a.i/ha with and without supplementary hoe-weeding, two hoe-weedings and weedy check. Sub-plot treatments consisted of eight cropping patterns [sole maize, maize-jackbean and maize-groundnut intercrops, each at two spacings (100 x 37.5 cm2 and 75 x 50 cm2) and sole crops of jackbean and groundnut]. All the weed control methods significantly reduced (p
Keywords: Keywords: intercropping, jackbeans, pre-emergence herbicide, weed control